HABITUS AND SYMBOLIC VIOLENCE ANALYSIS DEPICTED BY VIC VAN ALLEN IN THE FILM DEEP WATER (2022) - Alfaridzi, Javier Rayhan Ahmad; Santoso, Heri Dwi; Mutmainnah, Yulia (Universitas Muhammadiyah Lampung, 2025)
Abstract This study examines the portrayal of habitus and symbolic violence in the character of Vic Van Allen in the film Deep Water (2022), directed by Adrian Lyne. The research method used is descriptive qualitative, analyzing the film's narrative and semiotics to identify key scenes, dialogues, and non-verbal expressions that reflect the concepts of habitus and symbolic violence. The findings of this study indicate that Vic Van Allen's habitus is shaped by the accumulation of economic capital and a strong socio-cultural class, making him a calm and manipulative individual with significant control over his environment. This study highlights that symbolic violence, although invisible, has a profoundly destructive impact on victims and can perpetuate power imbalances in interpersonal relationships among the elite. Keywords: Habitus, Symbolic Violance, Vic Van Allen